Programmed intermittent epidural bolus improves efficacy of patient controlled epidural analgesia in postoperative pain management - Agung Senapathi, Tjokorda Gde; Gede Widnyana, I Made; Wiryana, Made; Mahaalit Aribawa, I Gusti Ngurah; Surya Panji, Putu Agus; Soetjipto, Sonni; Putra Pradhana, Adinda (Bali Journal of Anesthesiology, 2017)
Background: Postoperative acute pain will have negative impacts if not handled properly so it must be treated effectively. Patient Controlled Epidural Analgesia (PCEA) allows the patient to have an active role in determining the need of analgesia personally. Programmed Intermittent Epidural Bolus (PIEB) is a new method which proven better than Continuous Epidural Infusion. Ropivacaine has similar characteristic to Bupivacaine but with minimal cardiotoxic effect. Fentanyl as an adjuvant can accelerate the onset of action of local anesthetics in epidural analgesia. The purpose of this study was to compare the efficacy of PCEA+PIEB with PCEA as a modality of postoperative analgesia. Methods: Total 54 patients undergoing major surgery of the abdomen and lower extremities were divided into 2 groups randomly: PIEB+PCEA and PCEA. Then we did an evaluation of VAS, PCA demand, and total consumption of solution Ropivacaine 0.1% + Fentanyl 2Â  mcg/mL at 4Â hours, 8 hours, and 24 hours postoperative. Results: VAS at resting and at moving in both groups were found clinically comparable, although statistically, VAS at moving at 4 hours and 24 hours postoperative were lower in PCEA+PIEB group (p < 0.01). PCA attempted and PCA given were lower in PCEA+PIEB group (p â¤ 0.05). Total consumption of solution until 8 hours postoperative was comparable in both groups but at 24 hours postoperative it was much greater in PCEA+PIEB group (p < 0.01). Conclusions: PCEA+PIEB have greater efficacy than PCEA. VAS (atÂ resting and at moving), PCA attempted, and PCA given were lower in PCEA+PIEB group. Total consumption of solution RopivacaineFentanyl until 8 hours postoperative was comparable, but at 24 hours postoperative it was much greater in PCEA+PIEB group. In orthopedic surgery, VAS at resting was obtained below 30 mm in PCEA+PIEB group but VAS at moving was obtained in the category of moderate pain in both groups.